Inventory Of Randang Recipes In Sijunjung District As An Asset That Must Be Preserved - Pratiwi, Pratiwi; Elida, Elida (Universitas Negeri Padang, 2023)
This research is backgrounded because there is no data collection on randang in Sijunjung Regency as an asset that must be preserved which includes: various randang and randang recipes (ingredients, seasonings, processing equipment and processing processes). This type of research is qualitative, the location of the study was carried out in three sub-districts in Sijunjung Regency including: Kupitan District (plain area), Sumpur Kudus District (hilly area) and Lubuk Tarok District (lowland area) in December - January 2023. The source of research data was obtained from informants, namely Bundo Kanduang, a person who is an expert in making randang and a person who produces randang for commercialization. Data collection techniques through observation, interviews and documentation. The data analysis used is data reduction, data presentation and conclusions. The results of this study show that there are 9 kinds of randang, namely randang meat, randang ayam, randang pucuk ubi, randang paku / fern, randang bilalang, randang cubadak, randang jariang, randang baluik, and randang bungo jua. The ingredients are beef, chicken, yam tops, nails/ferns, bilalang meat, cubadak, jariang, baluik, bungo jua, potatoes and coconut milk. The spices are red pepper, cayenne pepper, onion, garlic, ginger, laos, lemongrass, turmeric leaves, orange leaves, and the spices used are coriander, cardamom, pekak, nutmeg, pepper, cloves and cinnamon. Equipment in the processing of randang are stale sanduak, furnaces and stale cauldrons. The randang processing process is carried out traditionally using firewood by means of diangai-sangai until dry blackish in color so that it can last a long time.